2023
DOI: 10.1111/jpc.16386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of hospitalised children with acute post‐streptococcal glomerulonephritis in the Top End of Australia

Abstract: Aims Despite the declining incidence of acute post‐streptococcal glomerulonephritis (APSGN) in Australia, there is still a significant burden of disease amongst Aboriginal and Torres Strait Islander people in the Northern Territory. Childhood APSGN has been highlighted as a predictor of chronic kidney disease in this population. We aimed to describe clinical characteristics and outcomes of hospitalised children with APSGN in the Northern Territory. Methods Single‐centre, retrospective cohort study of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Australian transplant policy already advocates for paediatric priority allocation; however, this study identified persisting inequity, and this requires an urgency for additive priorities for Aboriginal and Torres Strait Islander children. These priorities include preventing the onset of chronic kidney disease after acute kidney injury, 38 preventing diabetic nephropathy following young onset diabetes, and when their kidney function reaches end‐stage, prioritising health care models which support their access to dialysis, transplant waitlisting, and achieving early transplantation (especially within five years) 39 . These recommendations support the National Indigenous Kidney Transplantation Taskforce position statement, which references improving young peoples’ kidney health and wellbeing through transplantation 39…”
Section: Discussionmentioning
confidence: 99%
“…Australian transplant policy already advocates for paediatric priority allocation; however, this study identified persisting inequity, and this requires an urgency for additive priorities for Aboriginal and Torres Strait Islander children. These priorities include preventing the onset of chronic kidney disease after acute kidney injury, 38 preventing diabetic nephropathy following young onset diabetes, and when their kidney function reaches end‐stage, prioritising health care models which support their access to dialysis, transplant waitlisting, and achieving early transplantation (especially within five years) 39 . These recommendations support the National Indigenous Kidney Transplantation Taskforce position statement, which references improving young peoples’ kidney health and wellbeing through transplantation 39…”
Section: Discussionmentioning
confidence: 99%